The Implementation of the Community-Based Tourism Concept in Lingga Tourist Village, Karo Regency, North Sumatera - Sianipar, Rosianna; Rosdiana Pakpahan; Rudy Pramono (Yayasan Riset dan Pengembangan Intelektual, 2024)
Community-Based Tourism (CBT), a form of tourism operated by local residents for their own well-being, is the focus of this research. This study was conducted at a tourist destination located in Lingga Tourist Village, Karo Regency, North Sumatra. The purpose of this research is to uncover the tourism potential in Lingga Tourist Village and examine the application of Community-Based Tourism principles, as well as the supporting and inhibiting factors in managing tourism attractions in Lingga Tourist Village. This research uses a descriptive qualitative and quantitative approach, collecting both primary and secondary data. Primary data were collected through questionnaires, in-depth interviews, and observations, while secondary data were obtained from local government data through the Karo tourism department’s website. The findings indicate that overall, the CBT principles have been well-implemented in managing Lingga Tourist Village. Therefore, the research suggests that CBT principles have been applied at a high level in the Lingga Tourist Village destination. The local community is aware of the importance of involvement in managing their village as an attraction. The supporting factors for implementing CBT principles include natural resources, community contribution, local community involvement, and government support. Meanwhile, the inhibiting factors include the level of education and the readiness of the community